ANALYSIS OF FIGURATIVE LANGUAGE OF JALALUDDIN RUMI’S POEMS IN THE” BOOK OF LOVE POEMS” BOOK - Basuki, Edi Pujo; Saputri, Tiyas (Universitas Nahdatul Ulama Surabaya, 2021)
Maulana Jalaluddin Rumi Muhammad Hasin al-Kattabi al-Bakhri, known as Rumi, was born in Wakhsh (1207-1273). Rumi was an influential Sufi figure during his time, he was the number one teacher. Apart from that, he is also a poet. The poetry is widely known and popular in his era until now (Lewis, 2000). Figurative Language is a conspicuous departure from what user of a language apprehend as the standard meaning of words, or else the standard order of words, in order to achieve some special meaning or effect” (Abrams, 2012, p. 130). The method of this research is the descriptive approach. It determined the types of figurative language and described the figurative meaning. The source of data was taken from the first album of the poem of “The Book of Love Poems” by Jalaluddin Rumi. The main research of the study was writer himself as the main instrument. The figurative languages that the writer found were metaphor, simile, paradox, synecdoche, anaphora, personification, allusion, allegory, and alliteration. Stanzas which used figurative language of metaphors appears 51 times, simile was 16 times, paradox was 23 times, synecdoche was 10 times, anaphora appears 13 times, personification appears 8 times, allusion appears 5 times, allegory appears 31 times, hyperbole appears 3 times and alliteration appears 1 time. Rumi's professionalism as a poet could be seen in this Book of Love, which is in this case, he used various figures of speech so that his style of expression was not monotonous in conveying implied and explicit messages. There were several major themes that could be underlined from all the poetry titles in this book. Namely: (1) Out of Bound, (2) How to Find God, (3) Dissolve to God’s qualities (4) Unite with the God, (5) Love. All these major themes were captured by the author by classifying all poems based on systemic ideas. With the appointment of this theme, hopefully that it will become a recommendation for readers to read or not read it or even to research it further.